Does Corruption and MSMEs Affect The Corporate Income Tax (CIT) Rate in ASEAN Countries? - Agustin, Esther Sri Astuti Soeryaningrum; Pujarama, Riza A.; Indramawan, Dendy; Komaria, Nur (Jurnal Dinamika Ekonomi Pembangunan, 2023)
The corporate income tax rate is an important component of a country's tax revenue, especially in developing countries. Business entity taxes in ASEAN countries are different because they have different economic and political foundations. This study aims to determine the effect of the level of corruption, which is often an obstacle in business and the economy, and the number of MSMEs, which have a large proportion in the ASEAN economy. The sample used is of 10 ASEAN countries from 2011 to 2020. The method used is a panel model with random effects. The results show that corruption has a negative and significant effect on the level of corporate tax. The better the control of corruption in a country, the lower the level of corporate tax. Meanwhile, the number of MSMEs and GDP have no significant effect on the level of corporate tax. On the other hand, world oil prices have a positive and significant effect on corporate tax rates.